Infographics implemented by educative institutions: A review of its tendency and applications - Rivera Salas, Paola Eunice (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Objective: To describe the use of infographics in different areas of educational centers. Methodology: Mixed, descriptive, and non-experimental. Thirty-two research reports on the subject were retrieved. Also, examples of the different uses that educational institutions have made were identified. Results: The trend in research is to report on using infographics within the teaching-learning process. Although, the institutions have diversified their application in tutoring, institutional communication, and Schools for Parents. Conclusion: It is necessary to analyze the applications given in educational centers and encourage the use of interactive infographics.